Factors influencing emotional culture-based communication - ICHIM, Radu-Gabriel (Acta et Commentationes, Sciences of Education, 2025)
This article outlines a theoretical framework for Emotional Culture-Based Communication (ECBC) in educational contexts, addressing a pressing challenge in contemporary society. It involves the meaningful use of affective resources in pedagogical interactions. Pedagogical communication reflects the influence of teachers’ emotional competences (empathy, self-regulation, and openness to dialogue) on learners and the overall quality of communication. Recognized as core pedagogical competences, these abilities support learning, enhance students’ socio-emotional adjustment, and reduce psychological discomfort and difficulties in social interaction. ECBC also fosters balanced interpersonal relationships, as well as successful social and professional adaptation and integration. In contemporary society, intelligence is no longer limited to the cognitive domain but also encompasses emotional and social dimensions, which are essential for effective communication and the harmonious development of personality. For these reasons, the article identifies the main factors that promote the consolidation of communication principles grounded in the values of emotional culture.